2021
DOI: 10.3389/fcimb.2021.711153
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model of the Dynamics of Cytokine Expression and Human Immune Cell Activation in Response to the Pathogen Staphylococcus aureus

Abstract: Cell-based mathematical models have previously been developed to simulate the immune system in response to pathogens. Mathematical modeling papers which study the human immune response to pathogens have predicted concentrations of a variety of cells, including activated and resting macrophages, plasma cells, and antibodies. This study aims to create a comprehensive mathematical model that can predict cytokine levels in response to a gram-positive bacterium, S. aureus by coupling previous models. To accomplish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Since the proposed technique is an explicit predictor-corrector approach and second-order accuracy, it is faster and more efficient than a wide set of statistical and numerical methods discussed in the literature for solving general systems of mixed ODEs/PDEs modeling real-world problems [26,28,65] and references therein. Some data used in the simulations are taken from [71]. Both tables and graphs (Tables 3-4 and Figures 2-3) suggest that the approximate solutions (macrophages and cytokine expressions) increase until a maximum concentration, so called "peaks", after approximately t hours, and become constant when the antigens are eliminated by the immune response.…”
Section: Numerical Experiments and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the proposed technique is an explicit predictor-corrector approach and second-order accuracy, it is faster and more efficient than a wide set of statistical and numerical methods discussed in the literature for solving general systems of mixed ODEs/PDEs modeling real-world problems [26,28,65] and references therein. Some data used in the simulations are taken from [71]. Both tables and graphs (Tables 3-4 and Figures 2-3) suggest that the approximate solutions (macrophages and cytokine expressions) increase until a maximum concentration, so called "peaks", after approximately t hours, and become constant when the antigens are eliminated by the immune response.…”
Section: Numerical Experiments and Discussionmentioning
confidence: 99%
“…The graphs (Figures 2-3) also indicate that the body response varies based on the damage inflicted by the bacteria S. aureus. Because of the activation of cytokines in the human immune response, the numerical experiments are performed assuming low initial concentration of gram-positive bacteria S. aureus as discussed in [71]. However, high expressions of the pathogen S. aureus due to the tissue damage associated with endotoxicity of gram-positive bacteria provoke a fast increase in cellular and cytokine responses (see Figure 4).…”
Section: Numerical Experiments and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this scenario, numerous studies in recent years have aimed to describe the mechanisms of the immune response, and predictive models have been proposed [ 44 ]. Moreover, transcriptomic studies have found different responses in sepsis caused by Gram-positive compared to those caused by Gram-negative bacteria not only in adults but also in children and preterm infants [ 45 ].…”
Section: Immune Responsementioning
confidence: 99%